TEACHING BEYOND SOCRATES: AN EXPERIMENT WITH ICTS FOR AN UNDERGRADUATE COURSE OF BUSINESS ADMINISTRATION AT A UNIVERSITY IN SOUTHERN BRAZIL - Villar, Eduardo Guedes; Vilvert, Alex Sandro Steinheuser; Domingues, Maria Jose Carvalho de Souza (Revista de Negócios, 2016)
This research examined the influence of multimedia presentations on content retention and satisfaction of business administration students when subjected to different didactic standards. For this study we used experimental procedures with 147 undergraduate students of Business Administration at a university in southern Brazil. As for the retention of the contents, statistical differences were found between the experimental groups; classes with dynamic slides showed better results. As for the influences of teaching tools in students’ satisfaction, the survey indicated that dynamic slides facilitate theÂ logical and rational development of the discipline and raise students’ motivation. Traditional slides, in turn, can disperse the interest of the student andÂ suppress attention to the teacher.